Telomeres, A Busy Platform for Cell Signaling - Gardano, Laura; Pucci, Fabio; Christian, Larissa; Le Bihan, Thierry; Harrington, Lea (Frontiers in Oncology, 2013)
Telomeres are the terminal structures at the ends of linear chromosomes that represent a solution to the end replication problem. Specific binding of the six-protein subunit complex shelterin to telomeric, repetitive TTAGGG DNA sequences contributes to the stable architecture and maintenance of telomeres. Proteins involved in the DNA damage response are also localized at telomeres, and play a role in the surveillance and maintenance of telomere integrity. The enzyme responsible for telomere extension is telomerase, a ribonucleoprotein with reverse transcriptase activity. In the absence of telomerase, telomeres shorten to a length threshold that triggers the DNA damage response and replicative senescence. Here, we will summarize the latest findings concerning vertebrate telomere structure and epigenetics, and we present data regarding the impact of short telomeres upon cell signaling. In particular, in murine embryonic stem cells lacking telomerase, we found that distribution of cytosolic/nuclear ß-catenin, a key component of the Wnt signaling pathway, changes when telomeres become critically short. We discuss implications and future perspectives of the effect of epigenetic modifications and/or conformational changes of telomeres on cell metabolism and signaling networks. Such an analysis may unveil potential therapeutic targets for pathologies like cancer, where the integrity of telomeres is altered.